Improving Organisational Performance through Rewards in University Libraries in Ghana - Badu, Edwin Ellis (Ghana Library Journal, 2004)
The paper comments on some of the current motivation and reward practices available to the Ghanaian worker particularly the library staff of Ghana’s five public universities. A sample size of 100 was chosen from a population of 435 staff members to conduct a survey. Results indicate that improving performance through rewards is a highly complex process which takes a lot of effort to get right. The views of participants on how to improve pelfo rmance to a fair extent strengthens some of the motivation theories, for example, Maslow (1964), Herzbelg et al (1959) , Vroom (1964) and Adams (1965). It is concluded that for the university libraries to achieve best results it is necessary for library administrators to understand the process of motivation and how rewards can best motivate the workers and to appreciate the value of the different types of reward and how they can best be used.